Increasing The Urgency Of Understanding The Age Of Marriage In Order To Manifest Children’s Educational Rights At Ponpes Ar Rosyid Pemalang - Latifiani, Dian; Tasu'ah, Neneng; Widyawati, Anis; Novita, Yustina Dhian; Rasidah , Seni Ira Maya; Sani, Rahmawati Melati; Fuad, Choirul (Semarang State University Undergraduate Law and Society Review, 2025)
ABSTRACT. Islamic boarding schools are religious-based educational institutions with a focus on forming children’s morals and character as an effort to prevent children from falling into immorality which can obstruck the fulfillment of children’s educational rights to the maximum. The problem is that the survey results of the target community (Santri Islamic Boarding School Ar Rosyid) do not yet have an optimal understanding (17 respondents answered incorrectly) regarding marriage regulations as regulated in the Marriage Law, including regarding the minimum age limit for marriage. The target community also does not optimally understand the existence of alternative solutions for children dropping out of school due to child marriage, so that the right to education cannot be obtained optimally. Based on this concern, the author offered an alternative solution in the form of sustainable activities that focused on increasing the urgency of understanding the age of marriage in order to manifest children’s educational rights at the Ar Rosyid Pemalang Islamic boarding school. The target achievement is increasing the urgency of understanding the marriage age and educational forum solutions through post tests with higher correct answers than the survey results. The methods used to achieve the objectives of this service program are: (1) Coordination and survey of partner needs (2) legal counseling; and (3) Evaluation. The target audience for this service program are ordinary people who have not optimally understood and analyzed the urgency of understanding the marriage age so that basic education is fulfilled.